Balanced Scorecard Design for More Ensuring the Achievement of the Vision, Mission and Strategic Objectives of it Company - Steven Ignasius; J. Johny Natu Prihanto; Amanda Setiorini (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study examines the challenges and outcomes of implementing a Balanced Scorecard (BSc) particularly in the IT industry. By integrating academic research with real-world applications, this research identifies challenges and opportunities in the IT industries, to inform best practices for practitioners. Methodology/Approach: This research uses a qualitative approach with a case study method at one IT company. Data collection was done through interviews with six informants from various management positions, observation, and literature review. Data analysis used NVivo software to identify patterns and relationships in the interview results and develop a Balanced Scorecard (BSc) framework. Results/Findings: The study's results identified 11 strategic objectives consisting of 2 strategic in the learning & growth perspective, 3 strategic in the internal business process perspective, 3 strategic in the perspective and 3 strategic in the financial perspective. From these strategic objectives, KPIs, targets and initiatives are also discussed in this study. Conclusions: The findings indicate that implementing a Balanced Scorecard helps IT companies translate vision and mission into measurable strategic objectives and actionable KPIs. The proposed 11-objective BSc framework (with targets and initiatives) can strengthen strategic alignment, performance monitoring, and decision-making across the four perspectives. Limitations: This qualitative case study on Company IT has limited generalizability due to its focus on a single company and industry. Data collection via interviews and observations introduces potential researcher/respondent bias. Contribution: This research developed a Balanced Scorecard (BSc) framework for IT company strategy development. It includes four perspectives, eleven strategic objectives, KPIs with targets and supporting initiatives.